Aggiornamento católico e teologia da libertação no Brasil e no México: um estudo histórico-comparativo entre a revista de Cultura Vozes e a revista Christus (1966-1980) - Andreo, Igor Luis [UNESP] (2015)
The objective of this PhD Thesis is to present a historical-comparative study of the Revista de Cultura Vozes, from Brazil, and the Mexican magazine Christus, whose pages have been a locus for the dissemination in their respective countries of the peculiarities of the ideals of a significant number of intellectuals representatives of progressive Catholic renewal that occurred in Latin American territory from the 1960s. We propose to focus our analysis on the similarities, differences and changes made in the pages of both magazines in relation to the objectives, characteristics and limitations designed to achieve the social changes perceived as necessary, and also for the treatment and the changes related to the ways of thinking and dealing with ethnic and cultural diversity present in the Latin American subcontinent. We believe that our proposal is justified to contemplate two countries (Brazil and Mexico) that despite the great disparity number is represented as regards adherence to the sectors of Liberation Theology, were achieved significantly by the political and social consequences of this intellectual socio-theological movement